Teaching how to deliver bad news: a systematic review - Cavalari Camargo, Nicole (2019)
Abstract“Bad news”, defined as information with huge emotional valence and potential to change personal perspectives, is, by definition, a challenge for physicians. However, the subject is not always taught in medical schools. This systematic literature review compiles all articles regarding communication of bad news after researching in databases for “medical school” and “bad news” in English, Portuguese and Spanish. The criterion was to include articles that elucidated about teaching techniques. From all 313 papers, we included 27 and classified their strategies. Most results showed that mixed strategies are more common and that, in general, the subject is wellreceived and appreciated by students, who reported an improvement in communicative capability after the training. We conclude that all techniques are valid and medical schools should focus on integrating this training in their regular curriculum.